Chemical Constituents of Vitex Negundo and Evaluation of Their Anti-Inflammatory and Antioxidant Activities - Jamaludin, Fadzureena (2008)
Leaves and stem of Vitex negundo were examined for phytochemicals using various techniques such as normal column chromatography, gel filtration on Sephadex LH-20 and radial chromatography. From the leaves, seven compounds were isolated and identified, by the use of various spectroscopic methods, to be mixture of the flavonoids luteolin, luteolin-3’-O-glucuronide, and isoorientin, the iridoid glycosides 2’-p-hydroxybenzoylmussaenosidic acid and agnuside, and phydroxyl benzoic acid as well as stigmasterol and β-sitosterol. Meanwhile, the stem yielded four lignans which were isolated for the first time from the plant, identified as 6-hydroxy-4-(4-hydroxy-3-methoxyphenyl)3-hydroxymethyl-7- methoxy-3,4-dihydro-2-naphthaldehyde, vitedoin A, vitrofolal E and detetrahydroconidendrin.Nitric oxide (NO) inhibitory assay using RAW 264.7 murine macrophage and soybean lipoxygenase inhibitory assay were carried out in the screening for antiinflamatory properties of the crude methanolic extract, the hexane, dichloromethane and ethyl acetate soluble fractions of the plant. From the leaves, both the hexane and dichloromethane fractions were shown to strongly inhibit nitric oxide production with an IC50 of 14.00 g/ml and 20.00 g/ml respectively. Meanwhile, inhibition of soybean lipoxygenase activity was shown by the ethyl acetate fractions from both plant parts with IC50 of 56.38 g/ml and 63.94 g/ml respectively. Further anti-inflammatory investigation on some of the isolated compounds showed that luteolin was significantly inhibited NO production with an IC50 of 41.50 g/ml (145.10 M), and inhibited formation of (9Z, 11E)-(13S)-13- hydroxyoctadeca-9,11-dienoate with an IC50 of 1.55 g/ml (5.42 M). Luteolin also exhibited high activity in PAF receptor binding assay with 70.20% inhibition at concentration of 18.2 g/ml and xanthine oxidase assay with 98.20% inhibition at concentration of 100 g/ml. The antioxidant evaluation using DPPH radical scavenging assay showed that luteolin and 6-hydroxy-4-(4- hydroxy-3-methoxyphenyl)3-hydroxymethyl-7-methoxy-3,4-dihydro-2- naphthaldehyde at a concentration of 250 g/ml exhibited significant inhibition at 96.2% and 94.7% respectively. The results indicated that luteolin may play a key factor in the plant’s ability to reduce inflammation.